Effectiveness of computer-aided learning in oral health among patients and caregivers: a systematic review - Normaliza Binti Ab Malik; Jiaguan Zhang; Otto Lok Tao Lam; Lijian Jin; Colman McGrath (OXFORD UNIV PRESS, 2024)
Indexed by WOS/SCOPUS